KETERAMPILAN MENGAJAR ALUMNI PIAUD IAIN KUDUS DI LEMBAGA PAUD: PERSPEKTIF NEUROSAINS PENDIDIKAN ISLAM - Zakiyah Isnawati (LPPM IAD Probolinggo, 2026)
This study examines the teaching skills of graduates from the Early Childhood Islamic Education Study Program (PIAUD) at IAIN Kudus (cohorts 2019–2021) teaching in PAUD institutions in Jepara Regency, from the perspective of Islamic educational neuroscience. Using a descriptive qualitative design, data were collected through classroom observation, semi-structured interviews, and document analysis (observation sheets, lesson plans, photos). Ten teaching skill components were assessed. Quantitative summaries show cohort differences with total scores: 2019 (306), 2021 (292), 2020 (284). Weak components include pre-lesson conditioning and activity variation; strengths include explaining and small-group teaching. Findings recommend integrating neuroscience-based microteaching modules, stronger field mentoring, and instrument revision to better capture brain-friendly practices.